2022
DOI: 10.3389/fpubh.2022.954721
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of eosinophils and its correlated diseases

Abstract: Eosinophils are differentiated by bone marrow multipotent progenitor cells and are further released into peripheral blood after maturation. Human eosinophils can exhibit unique multi-leaf nuclear morphology, which are filled with cytoplasmic granules that contain cytotoxicity and immune regulatory proteins. In recent years, many studies focused on the origin, differentiation and development process of eosinophils. It has been discovered that the eosinophils have the regulatory functions of innate and adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 114 publications
1
5
0
Order By: Relevance
“…Although the WBC values were in accordance with the reference values available in the literature for capuchins, 16 were not for howler monkeys 21 (Table S3), thus we must consider intraspecific variations in WBC due to antigenic stimulation, stress during animal handling, and anesthesia. 21,77 In this study, males had significantly lower platelet counts than females in both species, which was similar to results described recently in spider monkeys. 78 Previous studies, although without significant difference, reported lower values for platelets in males in other platyrrhine species such as howler monkeys, 21,35,67 capuchin monkeys, 19,69,79 spider monkeys, 27 and in catarrhines including vervet monkeys (Chlorocebus aethiops sabaeus) 80 and long-tailed macaques (Macaca fascicularis) and rhesus monkeys (M. mulatta).…”
Section: Blood Parameterssupporting
confidence: 91%
See 2 more Smart Citations
“…Although the WBC values were in accordance with the reference values available in the literature for capuchins, 16 were not for howler monkeys 21 (Table S3), thus we must consider intraspecific variations in WBC due to antigenic stimulation, stress during animal handling, and anesthesia. 21,77 In this study, males had significantly lower platelet counts than females in both species, which was similar to results described recently in spider monkeys. 78 Previous studies, although without significant difference, reported lower values for platelets in males in other platyrrhine species such as howler monkeys, 21,35,67 capuchin monkeys, 19,69,79 spider monkeys, 27 and in catarrhines including vervet monkeys (Chlorocebus aethiops sabaeus) 80 and long-tailed macaques (Macaca fascicularis) and rhesus monkeys (M. mulatta).…”
Section: Blood Parameterssupporting
confidence: 91%
“…This result highlights the importance of analyzing differential WBC count to determine and establish the diagnosis of each clinical condition. Although the WBC values were in accordance with the reference values available in the literature for capuchins, 16 were not for howler monkeys 21 (Table S3), thus we must consider intraspecific variations in WBC due to antigenic stimulation, stress during animal handling, and anesthesia 21,77 …”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Recently, signi cant advancements have been made in the research of various cytokines in diseases [31,32]. Likewise, the roles and effects of eosinophils in various diseases have been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from pH-, redox-, and enzyme-responsive nanomedicines, bioresponsive materials are available in a wide range of various types and are employed in many diseases. When developing bioresponsive materials for disease treatments, endogenous variations are appealing targets since they are frequently significant markers for several sorts of diseases [108][109][110]. Meanwhile, other typical endogenous stimuli include glucose, ions, adenosine triphosphate (ATP), hypoxia, mechanical cues, as well as nucleic acids [111].…”
Section: Other Bioresponsive Materials For Various Diseasesmentioning
confidence: 99%